Adorno, politics, and the aesthetic animal - Basnett, Caleb J. (University of Toronto Press, 2021)
"Built upon the principle that divides and elevates humans above other animals, humanism is the cornerstone of a worldview that sanctifies inequality and threatens all animal life. Adorno, Politics, and the Aesthetic Animal analyses this state of affairs and suggests an alternative--a way for humanity to make itself into a new kind of animal. Theodor W. Adorno has been accused of leading critical theory into a blind alley, divorced from practical social and political concerns. In Adorno, Politics, and the Aesthetic Animal, Caleb J. Basnett argues that by placing the problem of the human/animal distinction at the centre of Adorno's thought, we discover a new Adorno, one whose critique of domination is in dialogue with classic concerns of political thought forged by Aristotle, including questions of humanist political education and the role of art. Through a close reading of primary sources, Basnett identifies the principal conceptual structure entwined with the understanding of human life as antagonistic to other animals, and outlines how forms of aesthetic experience disrupt this problematic concept in favour of a reconceptualization of what we call human. His analysis displaces the centrality of the human and attempts to open up a space for its transformation, both in terms of how humans relate to each other and in how humans relate to other animals."--